Pendidikan Karakter Berbasis Kearifan Lokal Adat Sunda “Ngalaksa” Tarawangsa di Rancakalong Jawa Barat - Kesuma, Guntur Cahaya (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Local  wisdom  contained  in  some  groups  /  minorities  or  indigenous  communities  in Indonesia contains a lot of cultural values  of the nation are still going strong into the identity of the character of their peoples. But on the other hand, the value of local knowledge is often overlooked,  because  they  do  not  correspond  with  the  development  era.  In  fact,  from  such wisdom could be promoted noble values which can be used as a model in the development of Indonesian culture. In this case the local wisdom of indigenous Sunda "Ngalaksa" Tarawangsa as  for  the  implementation  of  this  ceremony,  set  a benchmark wearing the national calendar that  always  falls  in  July,  while  the  determination  date is usually the result of an agreement between  the  local  government  and  community  elders  elements  that  will  hold  the  ceremony ngalaksa. Day ceremony, calculated and determined based on market day. The highlight of the event, the day 7, which must occur on the day kliwon market.Ceremony  "Ngalaksa"  held  within  the  framework  of  an  expression of gratitude to the Almighty  for  the  crops  that  have  been  acquired,  and  to  preserve  the  customs  of  society Rancakalong as the preservation of art and cultural heritage. "Ngalaksa a culture that contains the  value  of  the  noble  nation  that  really  needs  to  be  developed  in  order  to  strengthen  the nation's  identity  and  personality,  as  well  as  being  the  driving  government  programs  in  all fields".  Ngalaksa  culture  is  accompanied  by  music  Tarawangsa  and  jentreng,  stringed instrument similar fiddle and harp.The  values  of  character  education  that  can  be  taken  on  a  ceremonial  ngalaksa tarawangsa  on  society  Rancakalong,  is  tolerance,  democracy,  daring,  discipline,  hard  work, creativity, responsibility,  relegius,  environmental  care,  social  care,  the  national  spirit  and patriotism.